Measuring The Causes Factor Of The Criminal Act Of Persecution - Mohamad Rivaldi Pakaya (Universitas Negeri Gorontalo, 2020)
Abstract: This study aimed to find out the factors causing the occurrence of criminal acts of persecution. The method used in this research was empirical or sociological research methodology. This study used a case approach, which was carried out by examining cases related to the issues faced and sampling using purposive sampling. The results of this study indicated that the occurrence of criminal acts of persecution in the jurisdiction of the Batudaa Pantai Sector Police was caused by the influence of alcoholic beverages, an unfavorable environment, and low education which also affected thinking patterns, the heartache that led to revenge, misunderstandings resulting from failure communication process, to uncontrolled emotions. The Batudaa Pantai sector police should make more use of social media in providing understanding to the community and school children so that legal awareness continues to increase in all circles because they see the impact that will be caused if they commit a criminal act.Keywords: Cause; Criminal; Persecution